Applications of Modified Starches - Flores Huicochea, Emmanuel; Rendón Villalobos, Rodolfo (IntechOpen, 2018)
Starch is the main source of energy to humans, but starch today has other roles in food, packing and pharmaceutical industries like filler, emulsion stabilizer, coating, etc. The native form of starch has application limitations on broad range of temperature, pH and stability, among others, required on several industrial applications. The alternative way is modified starch to improve its properties and uses on several industrial fields. The book explores the use of physical and, chemical modifications and even the unusual modification using ionizing radiation on several sources of starch, the effect of them on the properties and application fields of modified starch.